Assessing the value of cooperative membership: A case of dairy marketing in the United States. Issue 1 (June 2021) - Munch, Daniel M.; Schmit, Todd M.; Severson, Roberta M.
Highlights: Dominance of cooperatives in some industries signals provision of value to members. Little is known about the monetary value of cooperative ownership and control rights. A discrete choice experiment to US dairy farmers reveals significant ownership value. Changing values across heterogeneous members informs improved governance practices. Abstract: The existence of cooperative organizations in today's business environment, particularly in agriculture, signals their continued ability to provide value to their member owners. However, due largely to data limitations, we know very little about the monetary value of ownership held by members and how value changes across members of differing characteristics. Through a discrete choice experiment with more than 200 dairy farmers in the United States, we examine these issues explicitly for dairy marketing cooperatives that purchase their members' milk and process it into finished dairy products. Results suggest that dairy farmers, on aggregate, are willing to accept lower per hundredweight compensation, 2.3% of the average milk price, to be cooperative members relative to selling to independent handlers. Results also suggest dairy farmers actively consider the industry wide impacts within pricing offers on preferences for other milk pricing attributes. The inclusion of demographic covariates highlights preferences important to understanding heterogeneous member interests and, thus, informing improved cooperative governance strategies and board decision making to address them.